Breaking down the US employment multiplier using micro-level data - Edoardo Briganti; Holt Dwyer; Ricardo Duque Gabriel; Victor Sellemi (Bank of Canada, 2025)
Using newly matched data on US defense contracts and restricted administrative employment data, we show that the employment effects of defense procurement are costly, concentrated and slow to diffuse. Large, existing contractors drive initial employment gains that come at a high cost of approximately US290,000 per job-year. While employment in non-contracting firms is crowded out on impact, positive spillovers emerge gradually and account for half of regional employment gains by the third year after a spending shock, suggesting delayed but persistent medium-term gains across industries. Among contractors, only 15% of job creation occurs at establishments that receive defense contracts, highlighting the role of supply chain linkages.
Keywords: E62; H57; J21; 330; Fiscal policy